2007
DOI: 10.1097/shk.0b013e318053621d
|View full text |Cite
|
Sign up to set email alerts
|

LYMPHATIC-BORNE IL-1β AND THE INDUCIBLE ISOFORM OF NITRIC OXIDE SYNTHASE TRIGGER THE BRONCHIAL HYPORESPONSIVENESS AFTER INTESTINAL ISCHEMA/REPERFUSION IN RATS

Abstract: Intestinal I/R (i-I/R) is an insult associated to further adult respiratory distress syndrome and multiple organ failure. This study was designed to evaluate the repercussions of i-I/R on bronchial reactivity to the cholinergic agent methacholine. Anesthetized rats were subjected to superior mesenteric artery occlusion (45 min) and killed after clamp release and defined intestinal reperfusion periods (30 min, 2, 4, or 24 h). Intestinal I/R caused a progressive bronchial hyporesponsiveness (BHR) that was maxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
11

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 32 publications
0
12
0
11
Order By: Relevance
“…*P < 0.05, **P < 0.01, ***P < 0.001. understanding of the role of thoracic lymphatic duct ligation in ALI due to intestinal I/R. We previously found that cytokines such as TNF-a, IL-1b, IL-10, and IL-6 were elevated in lymph obtained during the intestinal reperfusion period [17][18][19] and that IL-1b mediates bronchial hyporesponsiveness by inducing iNOS expression in the lung [24]. In the present study, we therefore investigated whether the lymph drained after intestinal I/R could stimulate lung production of inflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%
“…*P < 0.05, **P < 0.01, ***P < 0.001. understanding of the role of thoracic lymphatic duct ligation in ALI due to intestinal I/R. We previously found that cytokines such as TNF-a, IL-1b, IL-10, and IL-6 were elevated in lymph obtained during the intestinal reperfusion period [17][18][19] and that IL-1b mediates bronchial hyporesponsiveness by inducing iNOS expression in the lung [24]. In the present study, we therefore investigated whether the lymph drained after intestinal I/R could stimulate lung production of inflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%
“…Coelho et al [12 ] showed in an elegant study that intestinal ischemia and reperfusion caused an increased bronchial hyper-reactivity and that this distant effect was mediated via the lymphatic system. They occluded the mesenteric artery for 45 min and studied the effects of reperfusion periods ranging from 2 to 24 h. Bronchial hyper-reactivity was maximal after 2 h and returned to baseline after 24 h. Lymphatic duct ligation abolished the hyper-reactivity.…”
Section: Inflammatory Spread Via the Lymphatic Systemmentioning
confidence: 98%
“…Por causa disso, dois aspectos acerca da SDRA tornam seu estudo relevante: a falta de terapia medicamentosa eficaz e a alta taxa de mortalidade (LUH et al, 2007;LEWANDOWSKI e LEWANDOWSKI, 2006). Além disso, baseados em estudos do nosso laboratório (CAVRIANI et al, 2005;CAVRIANI et al, 2007;COELHO et al, 2007;BREITHAUPT-FALOPPA et al, 2009) e naqueles descritos para eventos traumáticos associados ao choque hemorrágico (DEITCH et al, 2001;DAVIDSON et al, 2004), lançamos a hipótese de que o intestino, sob sofrimento isquêmico, pode ser considerado um potente gerador de mediadores inflamatórios, os quais, uma vez drenados pelo sistema linfático, atingem a circulação pulmonar, comprometem a sua homeostasia, causam recrutamento de neutrófilos, edema, contribuindo para a lesão tecidual e para a disfunção pulmonar frequentemente observada na SDRA. Nesse sentido, a questão sobre os efeitos prolongados da reperfusão intestinal associados a distúrbios inflamatórios permanece aberta.…”
Section: Discussionunclassified
“…Uma possível explicação seria o papel da IL-1β na indução da IL-10, que por sua vez exerceria ação antiinflamatória modulando o dano pós I/R (SOUZA et al, 2003). Por outro lado, dados do nosso grupo mostraram que os níveis séricos de IL-1β estão elevados em ratos submetidos a I/R intestinal , e que sua neutralização previne a hiporreatividade brônquica induzida pela I/R intestinal (COELHO et al, 2007). Vale lembrar que o sistema linfático é importante via de ligação entre a IL-1β gerada pela I/R intestinal e a inflamação pulmonar observada.…”
Section: Isquemia E Reperfusão (I/r)unclassified
See 1 more Smart Citation